Information And Communication Technology: A Study Of Its Impact On Economic Growth In Malaysia - Ramlan, Jorah (2008)
The objective of this research is to measure and determine the impact of ICT on the economic growth of developing countries, using Malaysia as a case study, for the period 1965 to 2005. This research analyses four interrelated issues: (1) the identification of the economic structural transformation period, (2) the contribution of ICT in the periods before and after the economic structural transformation, (3) the causality effect of ICT on economic growth, and (4) the impact of ICT and human capital on total factor productivity.